Case-control study of an outbreak of acute toxoplasmosis in an industrial plant in the state of São Paulo, Brazil - Ekman, Claudio Cesar Jaguaribe; Chiossi, Maria Fernanda do Valle; Meireles, Luciana Regina; Andrade Júnior, Heitor Franco de; Figueiredo, Walter Manso; Marciano, Maria Aparecida Moraes; Luna, Expedito José de Albuquerque (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Foodborne diseases represent operational risks in industrial restaurants. We described an outbreak of nine clustered cases of acute illness resembling acute toxoplasmosis in an industrial plant with 2300 employees. These patients and another 36 similar asymptomatic employees were diagnosed with anti-T. gondii IgG titer and avidity by ELISA. We excluded 14 patients based on high IgG avidity and chronic toxoplasmosis: 13 from controls and one from acute disease other than T. gondii infection. We also identified another three asymptomatic employees with T.gondii acute infection and also anti-T. gondii IgM positive as remaining acute cases. Case control study was conducted by interview in 11 acute infections and 20 negative controls. The ingestion of green vegetables, but not meat or water, was observed to be associated with the incidence of acute disease. These data reinforce the importance of sanitation control in industrial restaurants and also demonstrate the need for improvement in quality control regarding vegetables at risk for T. gondii oocyst contamination. We emphasized the accurate diagnosis of indexed cases and the detection of asymptomatic infections to determine the extent of the toxoplasmosis outbreak.